Using printed texts to communicate information in the South African development context - Maritha Snyman (Communicare)
Brochures are often used in South Africa to disseminate information to disadvantaged communities. This article is based on a research project in which the effectiveness of printed texts containing information about agricultural practices was tested among a target audience of small-scale farmers in deep rural areas. The methodology used was informed by reception theory. The historical development of reception study is traced and compared with recent trends in communication research. The findings of this study indicate that considerable interpretation gaps exist between sender and receiver. This is mainly caused by a lack of understanding about the life world of the end-user and results in the absence of a common coda[ system between communicator and receiver. Empirical studies based on reception theory can make a positive contribution towards improving development communication in the pluralistic cultural and lingual South African society. It may well be used as an instrument to test the effectiveness of messages aimed at a specific target audience.